Subsecondary coding for individual identification of cattle through dermatoglyphics of muzzle - Mishra, Sharad; Tomar, Om Singh; Kalm, Ernst (The Indian Journal of Animal Sciences, 2012)
An investigation. was carried out in 6 breeds of cattle (602). viz. Sahiwal, Karan Swiss, Karan Fries, German Red and White and German Black and White, to develop subsecondary classification to strengthen the coding system through muzzle printing using modified cyclostyle ink procedure, for individual identification. An alphabetic code index was developed for pattern ridge ranging from 0 degree to 180 degree angles. The tinal code for subsecondary classification was developed by Â combining the alphabetic code of the pattern ridges of base sector, combination of extended pattern ridge angles and number of beads present in middle sector and Latin alphabets for upper sector. The code for the patterns of special category were developed by combining the pattern abbreviation and print number. The final code so developed was most effective to uniquely identify 89.70% animals based on pattern ridges, 5.80% animals based on distributed ridges and beads together, 3.82% animals based on distribution of beads only and 0.67% animals belonging to patterns, of special category. Thus, subsecondary classification gave a compact and unique coding system through muzzle printing for individual identificationof cattle.